PENINGKATAN KEMAMPUAN MENULIS CERPEN DENGAN PEMANFAATAN MEDIA KOMIK DIKELAS XI IPA NEGERI 2 LAWE BULAN TAHUN AJARAN 2021-2022 - Hidayah Munasti; Ati Rosmiati (STKIP USMAN SAFRI KUTACANE, 2022)
This research is to find out whether there is an increase in the ability to write short stories by using comics in the XI IPA class of SMA Negeri 2 Lawe Bulan in the 2021/2022 academic year. This type of research is quantitative research. Data were collected using tests for work in the pretest and posttest classes. The population in this study was 33 people. Data collection techniques were carried out in two meetings. First, before using comic media. Second, after using comic media. Data analysis technique. First, read short stories written by students. Second, converting comments into values. Third, describe the level of students' short story writing skills by finding the average. Fourth, clarifying the ability to write short stories before and after using comic media for class XI students of SMA Negeri 2 Lawe Bulan. The results of this study are First, the short story writing skills of class XI students of SMA Negeri 2 Lawe Bulan before using comic media obtained an average grade of 63.03 which was categorized as less. The ability to write short stories for class XI students of SMA Negeri 2 Lawe Bulan after using comic media obtained an average grade of 82.12 which was categorized as Good.